Diversity on the edge: non-linear patterns of coral community structure at an isolated oceanic island - Richards, Zoe; Ryan, N.; Harvey, Euan; Garcia, R.; Hobbs, Jean-Paul (Inter-Research, 2016)
Coral communities are expected to display predictable patterns of diversity and structure across depth and exposure gradients, yet these predictions have rarely been tested at oceanic locations. Here we tested 5 common ecological predictions about coral community structure at the remote Chrismas Island in the eastern Indian Ocean. Our results suggest that not all of the predictions hold true at this oceanic location, primarily because the community is structured in non-linear ways. Each surveyed depth zone (5, 12, 20 m) supported a distinctive community, yet species diversity and coral abundance did not show the expected linear increase with depth. Habitat complexity was also shown to respond non-linearly with depth, with the highest habitat complexity occurring in the intermediate 12 m zone. We discuss the ‘cliff-edge effect’ as a possible explanation for the high diversity and abundance of corals at 20 m, while physical stress and competitive exclusion may explain the low diversity at 12 m. The cliff-edge habitat provides a narrow zone in between the wave-swept shallows and the low light/high shade environment of the steep outer reef walls, and this zone of heterogeneous environmental conditions supports a wide diversity of corals. If future storm events, bleaching, disease or predator outbreaks were to impact the corals living in the cliff-edge habitat, this may have a disproportionate impact on the coral reef community as a whole. Monitoring the status of corals on the cliff edge is important for understanding and predicting how oceanic reef systems will be affected by climate change.